PENGARUH TINGKAT PENDAPATAN DAN KEPUASAN MENERIMA BEASISWA TERHADAP KEBAHAGIAAN PSIKOLOGIS MAHASISWA PROGRAM DUAL MODE SYSTEM DI STAI STAISTAI STAI PATI TAHUN 2013 - Ahmad Fatah (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractThis study aims to determine the effect of the level of income and satisfactionreceived scholarships to students of the psychological happiness Dual ModeSystem at the Islamic Institute of Pati in 2013, using a quantitative approachwith three variables: the level of income, the satisfaction of receiving a scholarship and psychological happiness. The study population was all students of the Dual Mode System totaling 117 students. Samples authors take 25% of polulasi, as many as 30 students. Analysis of this study using multiple regression with three steps: a preliminary analysis, hypothesis testing and analysis of further analysis. Results of this study was no effect of income level (X1) with psychological happiness (Y) student Dual Mode System in STAI Starch 2013. Thus the first hypothesis which says "There is a significant relationship between the income level of students to students of the psychological happiness Dual Mode system in sTAI Pati "is rejected. There is an effect of satisfaction received scholarships (X2) with psychological happiness (Y) student Dual Mode System in 2013. So STAI Pati second hypothesis ie "There is significant relationship between satisfaction received scholarships to students of the psychological happiness Dual Mode System in STAI Starch" accepted as true. The effect was of 18.3%, and the remaining 81.7% is influenced by other variables that have not been examined by the authors. No effect of income level (X1) and the satisfaction of receiving a scholarship (X2) with psychological happiness (Y) student Dual Mode System in 2013. So STAI Pati third hypothesis that "There is significant relationship between the level of income and satisfaction received a scholarship to happiness psychological student Dual Mode System d sTAI Starch "rejected.Keywoard: tingkat pendapatan, kepuasan menerima beasiswa, kebahagiaanpsikologis